The Relationship between Doomscrolling and Emotion Regulation with Anxiety of Adolescent Social Media Users in MAN 2 Mojokerto - Prima Permatasari; Diah Sofiah; Isrida Yul Arifiana (Kirana Publisher (KNPub), 2026)
This study aims to test the relationship between doomscrolling and emotion regulation and anxiety in adolescent social media users in MAN 2 Mojokerto. The phenomenon of doomscrolling, which is the habit of accessing negative information excessively, has become a concern in the context of adolescent mental health. Emotion regulation, as an individual's ability to manage emotional responses, is thought to have an important role in suppressing the negative impact of doomscrolling on anxiety. This study used a correlational quantitative approach, involving 237 3rd-grade students as participants. The instruments used included the doomscrolling scale, the emotion regulation scale (DERS), and the anxiety scale (RCMAS-2), all in Likert-scale format. The results of the data analysis showed a significant association between doomscrolling and emotion regulation and adolescent anxiety (R = 0.807; p < 0.01), with an explained variance of 65%. Partially, doomscrolling showed a significant positive association with anxiety (t = 4.115; p < 0.05), whereas emotion regulation showed a significant negative association (t = -14.433; p < 0.05). This suggests that the higher the intensity of doomscrolling, the higher the teen's anxiety levels; Conversely, the better the regulation of emotions, the lower the level of anxiety felt. These findings provide important implications for psychological interventions in helping adolescents manage healthy social media use and improve their ability to regulate emotions to reduce anxiety risk.